Dual Polarized Dual Fed Vivaldi Antenna for Cellular Base Station Operating at 1.7–2.7 GHz - Marko Sonkki; Sami Myllymäki; Jussi Putaala; Eero Heikkinen; Tomi Haapala; Harri Posti; Heli Jantunen (International Journal of Antennas and Propagation)
The paper presents a novel dual polarized dual fed Vivaldi antenna structure for 1.7–2.7 GHz cellular bands. The radiating element is designed for a base station antenna array with high antenna performance criteria. One radiating element contains two parallel dual fed Vivaldi antennas for one polarization with 65 mm separation. Both Vivaldi antennas for one polarization are excited symmetrically. This means that the amplitudes for both antennas are equal, and the phase difference is zero. The orthogonal polarization is implemented in the same way. The dual polarized dual fed Vivaldi is positioned 15 mm ahead from the reflector to improve directivity. The antenna is designed for -14 dB impedance bandwidth (1.7–2.7 GHz) with better than 25 dB isolation between the antenna ports. The measured total efficiency is better than -0.625 dB (87%) and the antenna presents a flat, approximately 8.5 dB, gain in the direction of boresight over the operating bandwidth whose characteristics promote it among the best antennas in the field. Additionally, the measured cross polarization discrimination (XPD) is between 15 and 30 dB and the 3 dB beamwidth varies between 68° and 75° depending on the studied frequency.